Time Course Evaluation of Reparative Cartilage with MR Imaging after Autologous Chondrocyte Implantation - Atsuya Watanabe; Yuichi Wada; Takayuki Obata; Takahisa Sasho; Takuya Ueda; Mitsuru Tamura; Hiroo Ikehira; Hideshige Moriya (Cell Transplantation, 2005)
The aim of this study was to evaluate the qualitative change in reparative cartilage after autologous chondrocyte implantation (ACI). Ten knees of 10 patients were studied. The signal intensities of reparative and normal cartilage were evaluated by fat-suppressed three-dimensional spoiled-gradient recalled (FS 3D-SPGR) MR imaging. The signal intensity (SI) index (signal intensity of reparative cartilage divided by that of normal cartilage) was defined and the change in SI index was investigated. Histological and biochemical evaluation was done at the second look arthroscopy. The SI index was at its lowest level immediately after ACI and increased with time to 9 months thereafter. After 9–12 months, the SI index settled to almost level and was maintained at that value for at least 2–3 years postoperatively. The average of the SI indexes after 12 months to the last examination was 74.2 ± 4.6 (range 64.2–82.8), which means signal intensity of reparative cartilage was maintained at a value lower than that of normal cartilage. The total ICRS score was 11.6 ± 2.3 points (mean ± SD). The GAG concentration was 107.9 ± 17.0 μg/mg (mean ± SD) in normal cartilage and 65.9 ± 9.4 μg/mg in reparative cartilage. The quality of reparative cartilage as hyaline cartilage was inferior to that of normal cartilage. In the present study, the time course change in the SI index indicates that the major maturation process of implanted chondrocytes neared completion in 9–12 months. Minor changes, such as matrix remodeling with reorganization of the collagen fibers in reparative cartilage, may continue, but an almost identical condition seemed to be maintained during the first 2–3 years of follow-up. SI index does not always reflect all properties of reparative cartilage but may be a useful parameter for noninvasive evaluation.